Water level reconstruction and characteristic diagnosis of China's largest freshwater lake for the past five hundred years. (30th August 2020) - Wan, Zhiwei; Gao, Zhendong; Chen, Xi; Zhang, Zhi; Liao, Fuqiang; Liu, Guangxu; Jia, Yulian; Jiang, Meixin
Abstract: The water-level variation of Poyang Lake, China's largest freshwater lake, has an important influence on the ecological and environmental protection of the middle reaches of the Yangtze River area. In addition, water-level variations will directly affect the lake's migratory bird habitat and migratory bird wintering. The reconstruction of the long-term Poyang Lake water-level variation series has important mitigation and adaptation significance for ecological protection and socio-economic development in the lake area. In this study, the historical records of drought floods from three representative regional stations of Poyang Lake were collected, and an OLS-PLS model was constructed for reconstruction. In this way, the water levels from the three regional stations were reconstructed for the past 500 years. The relationship between the water levels of the three regional stations and the Poyang lake water levels was analyzed using the partial least square (PLS) method, with R 2 = 0.490 (p < 0.001). The variations in water levels from 1500 to 2000 were then reconstructed based on this model, with a low relative bias of −0.19%. According to the results, there were nine periods of high water levels and nine periods of low water levels, among which 1604–1619 was the most obvious period of high water levels during the past 500 years and 1633–1647 was the most obvious period of low water levels. The results of the accumulated anomaly and the moving t -test revealed that a mutational point of water levels shift from high to low occurred in the year 1600. As can be seen from the results of the wavelet power spectrum, there were variations in the water levels with cycles of 2–4 years, 6–8 years, 10–12 years, 20 years, 38 years, and 128 years. The results of this study can be used for lake area ecological environment management and to mitigate the adverse effects of flood and drought disasters in the future.